Perceived Immune Status and Sleep: A Survey among Dutch Students. (10th September 2015) - Donners, Anouk A. M. T.; Tromp, Marilou D. P.; Garssen, Johan; Roth, Thomas; Verster, Joris C.
Abstract : Reduced immune functioning may have a negative impact on sleep and health, and vice versa. A survey among Dutch young adults (18–35 years old) was administered to collect information on perception of reduced immunity and its relationship to sleep disorders, sleep duration, and quality. Sleep disorders were assessed with the SLEEP-50 questionnaire subscales of sleep apnea, insomnia, circadian rhythm disorder, and daily functioning. Dutch young adults ( N = 574) completed the survey. Among them, subjects ( N = 209; 36.4%) reported perceived reduced immunity. Relative to those with a normal immune status, subjects reporting reduced immunity had significantly higher scores( p = 0.0001 ) on sleep apnea (2.6 versus 3.6), insomnia (5.1 versus 6.8), and circadian rhythm disorder (2.1 versus 2.7). Subjects reporting reduced immunity also had significantly poorer daily functioning scores (5.4 versus 7.6, p = 0.0001 ). No differences were observed in total sleep time, but those reporting reduced immunity had significantly poorer ratings of sleep quality (6.8 versus 7.2, p = 0.0001 ). Our findings suggest that perceived reduced immunity is associated with sleep disturbances, impaired daily functioning, and a poorer sleep quality. Experimental studies including the assessment of immune biomarkers and objective measures of sleep (polysomnography) should confirm the current observations.